Pengaruh Celebrity Endorse Dan Trust In Platfrom Terhadap Minat Menggunakan Grab Melalui Brand Awarness Sebagai Variabel Mediasi - Virgo Simamora; Widiastuti Widiastuti (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This study aims to examine the effect of Celebrity Endorser and Trust in Platfrom on Interest in Using Grab and Brand Awarness as a mediator. The population in this study is the Students of the University of August 17 Jakarta who already have income. The sampling technique uses the Random Sampling method. The amount of data is 80 respondents taken through a questionnaire using partial least square (PLS) data analysis. Based on statistical tests, the results of the study show that Selebrity Endorser significantly influences the Interest in Using Grab, Trust in Platfrom significantly influences the Interest in Using Grab, Brand Awarness significantly influences the Interest in Using Grab. Brand Awarness mediation has a significant effect and is to strengthen the influence of Celebrity Endorser on Interest in Using Grab. Brand Awarness mediation has a significant effect and is to reinforce the influence of Trust in Platform on Interest in Using Grab.Keywords: Celebrity Endorser, Trust in Platform, Brand Awarness, Interest in Using Grab.